The losing appeal of liberal democracy and the rise of populism - Richter, Norman (2019)
urpose: This master's thesis aims to examine a connection between the crisis of liberal democracy and the rise of populism. It focuses on the conceptual principles of democratic theory by Diamond, Held, Habermas, Sartori, Mudde, Kaltwasser, Katsambekis, Müller, Jesse and Dahrendorf, amongst others. Design: To recognise a decline of liberal democracy, democracy as a process and the importance of civil society have to be discussed in order to determine why liberal democracy is losing its appeal. The work of the above-mentioned scholars forms a framework for discussing the essential characteristics of liberal democracy and populism. The comparison of the European Parliament election results of 2014 and 2019 shows the different developments of populism. Germany, as a mature democracy is analysed according the conceptual principles of populism and whether electoral manifestoes of populist parties relate to democratic deficits. Results: The results show linkages between populism and the shrinking appeal of liberal democracy, as well as a slight rise of populistic parties within the EU. Universal requirements for populism were worked out and applied to verify the German AfD and the Left towards their populistic extent. Their electoral manifestoes for the 2017 German parliamentary elections show direct linkages to democratic deficits and in particular to the European Union. A discourse analysis of the legitimisation of democratic deficits reveals different perspectives. Research limitation: Due to its practical relevance and for a better scientific containment, this thesis focuses on liberal democracy relating to left- and right-wing populism. Germany is the only European Union country used as a case example. Analyses of centrist populism is possible for a comparison of results. Furthermore, this thesis has the potential to discuss existing models of democracy in order to find ways to measure democratic deficits. Practical implications: Today the buzzword populism often carries negative connotations in Europe when viewed as damaging to liberal democracy. However, as populism is a complex phenomenon this work also shows its positive effects and offers various perspectives on it. Most important is the finding that liberal democracy is losing its appeal, which has a growing impact on the rise of populism. The findings of a link between populism in Germany and the German perspective on democratic deficits at EU institutional level, may stimulate new discussions on how to react to populism and increase the quality of EU democracy.